Impaired planning but intact decision making in early Huntington's disease: implications for specific fronto-striatal pathology. - Watkins, L; Rogers, R; Lawrence, A; Sahakian, B; Rosser, A; Robbins, T (2000)
Previous neuropsychological data have suggested that deficits in early Huntington's disease (HD) include executive impairments, which often are linked with frontal-lobe dysfunction. This study sought to investigate the profile of cognitive deficits using two computerised tasks whose performance is known to rely on intact functions of separate areas of the prefrontal cortex. Twenty patients with early HD and 20 matched controls were given the one-touch Tower of London, a stringent measure of visuo-spatial planning, and a decision making task, which involved selecting and gambling on outcomes on the basis of their differing probabilities. Patients were significantly less accurate than controls on the planning test, which is sensitive to frontal lobe lesions and is strongly associated with the dorsolateral prefrontal cortex in functional imaging studies. On the decision making task, patients were unimpaired on the quality of their decision making, in contrast to previous reports of impairment on this task in patients with ventromedial prefrontal cortex lesions. This dissociation of performance is discussed in terms of the usual path of progression of HD through the striatum and the resultant pattern of disruption of the functioning of the different cortico-striatal functional loops.